Cunegonde's kidnapping: a story of religious conflict in the age of enlightenment - Kaplan, Benjamin J. (The Lewis Walpole series in eighteenth-century culture and history, 2014)
In a remote village on the Dutch-German border, a young Catholic woman named Cunegonde tries to kidnap a baby to prevent it from being baptized in a Protestant church. When she is arrested, fellow Catholics stage an armed raid to free her from detention. These dramatic events of 1762 triggered a cycle of violence, starting a kind of religious war in the village and its surrounding region. Contradicting our current understanding, this war erupted at the height of the Age of Enlightenment, famous for its religious toleration.0This book tells in vivid detail the story of this hitherto unknown conflict. Drawing characters, scenes, and dialogue straight from a body of exceptional primary sources, it is the first microhistorical study of religious conflict and toleration in early modern Europe. In it, Benjamin J. Kaplan explores the dilemmas of interfaith marriage and the special character of religious life in a borderland, where religious dissenters enjoy unique freedoms. He also challenges assumptions about the impact of Enlightenment thought and suggests that, on a popular level, some parts of eighteenth-century Europe may not have witnessed a rise of toleration.